2016
DOI: 10.1002/ppul.23548
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphisms with susceptibility to childhood asthma: A meta‐analysis

Abstract: ApaI polymorphism plays a particular role in childhood asthma in Asians. FokI polymorphism may be connected with pediatric asthma in Caucasian population. And BsmI polymorphism marginally contributes to childhood asthma susceptibility, while there might be no association between TaqI polymorphism and childhood asthma risk. Pediatr Pulmonol. 2017;52:423-429. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
3
24
1
10
Order By: Relevance
“…In the past few years, research on the correlation between VDR and asthma has focused on four SNPs: ApaI, FokI, BsmI and TaqI. Our meta-analysis showed that ApaI, FokI, and BsmI polymorphisms contribute to childhood asthma susceptibility, while there was no evidence of the association between TaqI SNP and pediatric asthma risk, which con rms the previous research results 70 . And we found that ApaI and BsmI polymorphisms may be associated with asthma in Asian populations.…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 86%
“…In the past few years, research on the correlation between VDR and asthma has focused on four SNPs: ApaI, FokI, BsmI and TaqI. Our meta-analysis showed that ApaI, FokI, and BsmI polymorphisms contribute to childhood asthma susceptibility, while there was no evidence of the association between TaqI SNP and pediatric asthma risk, which con rms the previous research results 70 . And we found that ApaI and BsmI polymorphisms may be associated with asthma in Asian populations.…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 86%
“…Of the four SNPs identified, Apal polymorphism is believed to play a role in childhood asthma in Asians, Fokl polymorphism may relate to pediatric asthma in Caucasians, Bsml polymorphisms marginally contributes to susceptibility of childhood asthma and no association was found between Taql and risk of pediatric asthma. 41 …”
Section: Childrenmentioning
confidence: 99%
“…In addition, they have reported that FokI polymorphism may be connected with pediatric asthma in Caucasian population and BsmI polymorphism marginally contributes to childhood asthma susceptibility. 27 In another meta-analysis evaluating 8 case-control studies, FokI, TaqI, and BsmI VDR polymorphisms were significantly associated with an increased risk of asthma in some populations. In this meta-analysis, the authors suggested that serum 25(OH)D levels and various environmental factors could modify the effect of these polymorphisms on asthma development.…”
Section: Discussionmentioning
confidence: 99%